RNAi-mediated barrier modulation: synergies of the brain and eye. (October 2010) - Hanrahan, Finnian; Humphries, Peter; Campbell, Matthew
Efficient drug delivery to the brain or the eye remains a key challenge for future therapies directed against neurodegenerative disorders. Indeed it has been estimated that up to 98% of clinically relevant drugs will not diffuse across the endothelial cells associated with the delicate microvasculature of the brain and inner retina. Using RNAi-based methods for suppression of claudin-5, a molecular constituent of the tight junctions associated with both the blood–brain and inner blood–retina barriers, it has been shown that these barriers can be rendered transiently and size-selectively permeable to molecules up to approximately 1 kDa. This review will discuss the principles upon which this technology is based and the potential therapeutic applications with regard to neurodegenerative disorders as well as common retinopathies.